Sosialisasi dan Edukasi Pemanfaatan Daun Salam (Syzygium polyanthum Wight.) untuk Meningkatkan Pengetahuan Masyarakat di Kelurahan Bangsal - Winartiana; Maharani Dwi Pratiwi; Tantik Tandela (ADIMASKA (JURNAL PENGABDIAN MASYARAKAT KESEHATAN), 2025)
Bay leaves (Syzygium polyanthum Wight.) are an herbal plant widely used as a cooking spice and have potential health benefits. However, their utilization by the community is still limited due to a lack of knowledge about their benefits and processing methods. The results of this activity showed that 18 community members (60%) had poor knowledge regarding the use of bay leaves, while 53.33% had good knowledge. The main problem faced by the community partner is the limited understanding of optimal utilization of bay leaves. Therefore, this community service activity aims to increase public knowledge about the benefits and potential uses of bay leaves. The method used was identifying the level of community knowledge through an educational approach. This activity is expected to contribute to the development and application of science and technology from higher education institutions to the community, while raising awareness about the use of local herbal plants to support health and well-being.